Strategi Humas MTA Surakarta dalam Sosialisasi MTA Tv Kepada Masyarakat - Danu Anggoro; Rahmat Wisudawanto; Dyah Retno Pratiwi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the communication strategies implemented by the public relations department of the Surakarta Al-Qur'an Interpretation Council (MTA) in promoting MTA TV to the public. MTA TV, as a medium for preaching, plays an important role in spreading Islamic teachings in accordance with the Qur'an and Sunnah. This study uses a qualitative descriptive approach with data collection through in-depth interviews, observation of social media, and documentation of promotional materials. The results show that the MTA Surakarta public relations department implements a communication strategy that includes five stages: research, planning, implementation, measurement, and reporting. In the research stage, MTA Surakarta's public relations conducts research to determine the preferences of the community. In the planning stage, MTA's public relations holds monthly meetings to plan da'wah programs. The implementation stage is carried out through various media, including radio, television, and social media, which are intensively promoted on digital platforms. In the measurement stage, MTA's public relations uses the “Halo Mediaku” program to receive feedback from the audience. The reporting stage involves the community in evaluating the quality of the broadcasts. This study shows that the communication strategy of MTA Surakarta's public relations has been implemented well, but it is recommended that audience research be further improved and interactive digital platforms such as live streaming be utilized to reach a wider audience